2017
DOI: 10.18869/nrip.jamsat.3.2.61
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Movement Activities in Synchronization With Music on Motor Proficiency of Children With Autism

Abstract: Objectives: Although social deficits are the main features of autism, children in autism spectrum disorder often too display difficulties with posture, coordination and motor planning. As such, poor motor skills are believed to be associated with greater difficulties in social communication. Some recent studies show that music can improve the sensory processing and motor functions by affecting brain connectivity. The present study aims to examine the effect of movement activities in synchronization with music … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…The obtained results suggested that music therapy interventions along with play therapy significantly increased the motor skills of experimental group compared to the controls. The positive effects of music in the motor coordination of children with ASD have been confirmed in previous research studies [13,[25][26][27][28], as well.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…The obtained results suggested that music therapy interventions along with play therapy significantly increased the motor skills of experimental group compared to the controls. The positive effects of music in the motor coordination of children with ASD have been confirmed in previous research studies [13,[25][26][27][28], as well.…”
Section: Discussionsupporting
confidence: 76%
“…The play therapy was planned and performed based on the disorder. The music therapy program along with the motor activities have been extracted from the musical composition program and the movement of Matthews Moreno et al [24] and the program of 'the effect of movement activities in synchronization with music' by Atigh et al [13].…”
Section: The Educational Programmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to a control group who took part in non-musical movement activities. Eleven children with low functioning autism who received musically synchronised movement exercises over an 8-week period showed significant improvements in motor skills, such as balance and upper limb coordination as measured by the Bruininks-Oseretsky test of motor proficiency (Atigh, Akbarfahimi, & Zarei, 2017). This study therefore suggests that musical accompaniment during physical exercises enhances motor skill learning of children with autism.…”
Section: Motion Sensor Devicesmentioning
confidence: 66%
“…Children with these disorders have numerous compromised areas, including motor proficiency [6]. A compromised motor skill makes it difficult for these children to perform dayto-day activities competently [7], including coordination, dexterity, balance, posture, gait, strength, speed, and agility [8]. However, it is a fact that these complications are not left unattended and have been addressed using numerous effective physical therapy techniques such as neurodevelopmental therapies [9], strength conditioning [10,11], balance and vestibular training [12], goal-directed motor learning [13], and virtual reality [14].…”
Section: Introductionmentioning
confidence: 99%